Perancangan Penangkap Debu (Wet ScrubberUntuk Penanganan Lanjut Debu Terbang Pabrik)Briket Arang "Aneka Sinendo" Ploso, Banguncipto,Sentolo, Kulonprogo,Daerah Istimewa Yogyakarta - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
ABSTRACT PT Aneka Sinendo produces charcoal briquette from wood mill saw. Fly ash coming from the dryer pollutes the environment, and then the effort to prevent this fly ash dispersion is needed. At the previous Vucer Program (Mindaryani, 1998), an additional cyclone has been constructed and 450 kg/day of fly ash can be recycled. Therefore the factory could save Rp 810.000,-/month to pay the electricity. As the pressure drop in the added equipment is very small while the fan is too big, the bin is needed to reduce the velocity into the extruder. From this evaluation, in order to trap all the dust out, a bag filter might be an alternative, as well as to use the excessive power of the fan. A bag filter has also been erected in the plant (Mindaryani, 2001) to solve this problem. As there was tar in the effluent gas, the filter was blocked. The filters should be changed every time, but the bag filter position is on the roof, so it is difficult to do this job. In order to solve this problem, a wet scrubber need to be constructed, this program would assist them in evaluating and design the equipment better, based on the engineering point of view. A wet scrubber system consists of a wet scrubber, pump and water circulation pond was also constructed in the plant. Wet scrubber construction next to the bag filter box reduced the fly ash and tar from the gas disposal and needs a little power for water circulation. The result of this activity is useful for the environment and especially for the factory worker. The partner from industry may apply this system and disseminate to other factories with the same problem to prevent the environmental pollution. Keywords:Penangkap Debu, environmental pollution